Follow-up of metal-on-metal hip arthroplasty patients is currently not evidence based or cost effective - Matharu, G; Mellon, S; Murray, D; Pandit, H (Elsevier, 2015)
Over one-million patients worldwide have received metal-on-metal (MoM) hip arthroplasties with a significant proportion requiring revision surgery in the short-term for adverse reaction to metal debris (ARMD). Worldwide authorities have subsequently issued follow-up guidance for MoM hip patients. This article compares follow-up guidelines for MoM hips published by five worldwide authorities, analyses these protocols in relation to published evidence, and assesses the financial implications of these guidelines. A number of major differences exist between authorities regarding patient follow-up, with vast cost differences between protocols (£84 to £988/patient/year for stemmed MoM hips and £0 to £988/patient/year for hip resurfacing). Current worldwide guidance is neither evidence-based nor financially sustainable with most protocols lacking the sensitivity to detect asymptomatic ARMD lesions.